Trends in occupational diseases in Finland, 1975–2013: a register study - Oksa, Panu (BMJ Open, 2019)
OBJECTIVES: The objective was to investigate trends in the incidence of recognized and suspected cases of occupational diseases in Finland from 1975 to 2013, including variations by industry – and describe and recognize factors affecting variations in incidence. DESIGN: A register study. SETTING: The data consisted of recognized and suspected cases of occupational diseases recorded in the Finnish Registry of Occupational Diseases (FROD) in 1975–2013. PARTICIPANTS: Altogether 240 000 cases of suspected and recognized ODs were analysed. PRIMARY AND SECONDARY OUTCOME MEASURES: From the annual workforce statistics and FROD data, we calculated the incidence of ODs and suspected ODs per 10 000 employees. For time trends by industrial sector, we used a 5-year moving average and a Poisson regression analysis. RESULTS: Annual average rates of ODs have varied from year to year. The total number was 25.0/10 000 employees in 1975 and 20.1/10 000 employees in 2013. Screening campaigns and legislative changes have caused temporary increases. When the financial sector was the reference (1.0), the highest incidence rates according to industrial sector were in mining and quarrying (9.87; 95% CI 8.65 to 11.30), construction (9.11; 95% CI 9.98 to 10.43), manufacturing (9.04; 95% CI 7.93 to 10.36) and agriculture (8.78; 95% CI 7.69 to 10.06). There is a distinct decreasing trend from 2005 onwards: the average annual change in incidence was, for example, −9.2% in agriculture, −10.3% in transportation and −4.7% in construction. The average annual decline was greatest in upper limb strain injuries (−11.1%). CONCLUSION: This study provides a useful overview of the status of ODs in Finland over several decades. These data are a valuable resource for determining which occupations are at an increased risk and where preventive actions should be targeted. It is important to study long-term trends in the statistics of ODs to see beyond the year-to-year fluctuations.